2015
DOI: 10.1111/iep.12163
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Mesna and n‐3 polyunsaturated fatty acids ameliorates experimental ulcerative colitis in rats

Abstract: Oxidative damage is a central feature of ulcerative colitis. Here, we tested whether the antioxidant Mesna, when administered alone or in combination with n-3 polyunsaturated fatty acids (n-3 PUFAs), affects the outcome of dextran sodium sulphate (DSS)-induced ulcerative colitis in rats. After the induction of colitis, DSS-treated rats were further treated orally (p.o), intraperitoneally (i.p) or intrarectally (i.r) for either 7 or 14 days with Mesna, n-3 PUFAs or both. Rats were euthanized at the end of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
3
11
0
1
Order By: Relevance
“…Cell death and up-regulated caspase 3-positive cells in the intestinal mucosa has also been reported to be involved in the development of DSS-induced colitis. [18][19][20] ELE has been shown to suppress H 2 O 2 -induced rat osteoblastic MC3T3-E1 cell apoptosis by inhibiting the expression of caspases 3, 6, 7, and 9. 21) Therefore, it is likely that ELE administration may suppress cell death of intestinal mucosal cells as a potential mechanism for its anti-colitis effect.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death and up-regulated caspase 3-positive cells in the intestinal mucosa has also been reported to be involved in the development of DSS-induced colitis. [18][19][20] ELE has been shown to suppress H 2 O 2 -induced rat osteoblastic MC3T3-E1 cell apoptosis by inhibiting the expression of caspases 3, 6, 7, and 9. 21) Therefore, it is likely that ELE administration may suppress cell death of intestinal mucosal cells as a potential mechanism for its anti-colitis effect.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloperoxidase is a 140-kDa heme protein secreted primarily by neutrophils and stored in eosinophils 38 , 39 . Colonic injury leads to the activation of neutrophils and macrophages, and the release of MPO from activated neutrophils causes hydrogen peroxide (H 2 O 2 ) to produce hypochlorous acid (HOCl) and chlorine anions (Cl − ) to further damage the colon 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar mechanism, mesna protects kidney tissue against ischemia/reperfusion injury induced by oxidative damage [51]. It has also shown that mesna significantly reduces colorectal tissue damage when administered orally or intraperitoneally by reducing oxidative stress, inflammation and apoptosis, likely through a mechanism that involves the inhibition of NF-κB and overexpression of iNOS [30]. Consistent with these results, we show that mesna is a potent inhibitor of MPO with an IC 50 of 5 μM.…”
Section: Discussionmentioning
confidence: 99%